Penanaman Nilai-nilai Islami untuk Generasi Z dalam Pemanfaatan Digital di Era 5.0 - Husin, Malik (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid advancement of digital technology in the Society 5.0 era has significantly affected human life, especially among Generation Z who are deeply immersed in digital media. This condition poses moral and spiritual challenges due to uncontrolled information exposure. This study aims to explore how Islamic values are instilled in Generation Z in utilizing digital technology. A qualitative descriptive approach was employed using observation, in-depth interviews, and documentation conducted in Rejosari Village, Indragiri Hulu Regency, Riau. Participants consisted of junior and senior high school students, teachers, and religious figures. The findings reveal that Generation Z demonstrates high digital literacy but lacks moral and ethical awareness. The strategies for instilling Islamic values include integrating Qur’anic teachings, fostering digital ethics, and utilizing Islamic media platforms such as podcasts and YouTube channels. Evaluation results indicate positive behavioral changes, including improved ethical conduct, digital responsibility, and social empathy after Islamic value reinforcement. The study concludes that Islamic values serve as an essential moral filter for the younger generation in navigating digital globalization. The implications highlight the importance of collaboration between schools, families, and communities to build a digital ecosystem grounded in Islamic values, forming digitally intelligent and morally upright individuals.